(untitled) (Scientia Agricola, 2018)
Fe-rich Oxisols on mafic rocks in Brazil generally have high magnetic susceptibility with high contents of some trace elements. These are taxonomically similar soils; however, differences in magnetic and geochemical properties may affect agricultural or environmental usability and subsequent management. This study investigated the pedogenesis of Fe-rich Oxisols from various parent materials and evaluated the lithogenetic influence on magnetic susceptibility and trace elements contents. Soil samples were collected from Bw horizons in 13 Rhodic Oxisols and a Typic Oxisol developed from several parent materials in Minas Gerais State, Brazil. Soils were analyzed by X-ray diffractometry (XRD) and magnetometry. Soil chemical analyses consisted of sulfuric and total (tri-acid) digestions and selective Fe oxides dissolutions and statistical correlations were determined. Fe-rich Oxisols presented a typical mineralogical composition of highly weathered soils with structural stability. The results confirm the difficulty to identify accurately magnetic minerals in different grain sizes using XRD. However, coarse fractions still exert dominant influence on the magnetic properties of the Fe-rich Rhodic Oxisols. In addition, coarse fractions probably contribute to the enrichment of superparamagnetic particles for the clay fraction. Although highly weathered, Fe-rich Oxisols may have their geochemical attributes still controlled by the parent material, where trace elements seem to be correlated with the magnetic minerals in the coarse fractions. Thus, the natural replacement of some trace elements from soil-solution equilibrium reactions during plant development could be more effective in soils with higher magnetic particles concentrations in the coarse fractions.